Empathic Leadership in Times of Disruption: A Case Study on Strategies to Sustain Employee Wellbeing - Dipoatmodjo, Tenri Sayu Puspitaningsih (Malaqbi Publisher, 2025)
In an era of relentless disruption, organizations face mounting pressure to safeguard employee well-being during transformative change. This qualitative case study investigates how empathic leadership sustains employee resilience in a technology-driven company undergoing structural reorganization. Drawing on in-depth interviews with 12 leaders and team members, the study identifies four key empathic behaviors: active listening, emotional validation, transparent communication, and personalized support. Findings reveal that leaders who consistently practice these behaviors foster psychological safety, mitigate burnout, and enhance collective adaptability. Participants emphasized that empathy transformed uncertainty into a shared challenge, with teams reporting heightened trust and collaboration. However, the research also uncovers tensions, including cultural biases that equate empathy with leniency and systemic barriers to personalizing support amid productivity demands. The study contributes to leadership and organizational behavior literature by framing empathy as a moral virtue and a strategic capability critical for navigating volatility. It calls for institutionalizing empathy through training, policy alignment, and metrics that value relational labor. Empathy leadership emerges as a scaffold for sustainable resilience by humanizing disruption, ensuring organizations thrive without sacrificing employee humanity.